A pyro-hydrometallurgical process for the recovery of alumina from waste aluminium dross. (15th June 2019) - Tripathy, A.K.; Mahalik, S.; Sarangi, C.K.; Tripathy, B.C.; Sanjay, K.; Bhattacharya, I.N.
Graphical abstract: Highlights: Dross was processed through pyro-hydrometallurgical route for alumina recovery. Aluminium mostly present in the forms of AlN, Al2 O3 and some in metallic aluminium in dross. Alkali leaching followed by soda roasting showed alumina leaching efficiency of ∼90%. A process flow sheet was developed for the production of alumina from aluminium dross. Abstract: To maintain a balance between sustainable development in the industries and natural environment, recycling of metal values is essential part of the ecosystem. In this aspect recycling of waste aluminium dross is of great importance. Dross formation is accomplished by natural oxidation of molten aluminium essentially on the surface of the melt while reclaiming particularly the secondary metal. In this work main focus was to develop a suitable process flow sheet for the production of pure alumina from waste aluminium dross. The method followed was soda – roast and dilute alkali leaching route and employing certain purification steps. About 90% recovery of alumina was obtained. The main advantage of the process was the recycling of the chemicals used in the system. The aluminium hydroxide obtained was bayerite in nature. This hydroxide can be utilised as the precursor material for obtaining different varieties of activated alumina through heat treatment for their use in non-metallurgical applications. A tentative cost analysis has been provided based on laboratory scale data.